2011
DOI: 10.1016/j.juro.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Intake, and the Risk of Stress, Urgency and Mixed Urinary Incontinence

Abstract: Purpose Although caffeine consumption is common, and is generally believed to affect bladder function, little is known regarding caffeine intake and incident urinary incontinence. Materials and Methods We conducted a prospective cohort study of 65,176 women without incontinence, aged 37–79 years, in the Nurses’ Health Studies. Incident incontinence was identified from questionnaires, during 4 years of follow-up. Caffeine intake was measured using food frequency questionnaires administered prior to incontinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 14 publications
2
46
1
6
Order By: Relevance
“…Improvements in incontinence after bariatric surgery may also have resulted from positive changes in lifestyle (increased physical activity) 39,40 or dietary composition (decreased bladder irritants such as caffeine). 41 …”
Section: Discussionmentioning
confidence: 99%
“…Improvements in incontinence after bariatric surgery may also have resulted from positive changes in lifestyle (increased physical activity) 39,40 or dietary composition (decreased bladder irritants such as caffeine). 41 …”
Section: Discussionmentioning
confidence: 99%
“…Dalosso et al found no association between tea or coffee consumption and stress UI or overactive bladder symptoms in the 39,603 male and female participants in the Leicestershire MRC Incontinence Study in the UK [17]. More recently, Jura et al recently reported data from the Nurses' Health Study characterizing measured caffeine intake and the presence of UI [18]. Their conclusion that high caffeine intake(>450 mg/day)was associated (RR 1.3, 95% CI 1.0, 1.8) with frequent UI (≥weekly) and urgency UI (RR 1.42, 95% CI 1.04, 1.95) is similar to our findings that caffeine intake ≥204 mg/day was associated any UI (OR 1.47, 95% CI 1.07, 2.01).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and clinical cohort studies have demonstrated mixed results regarding the relationship of caffeine and fluid intake on UI in women [12][13][14][15][16]. Two large epidemiologic studies found conflicting conclusions on whether caffeine impacts incontinence [17,18]. Little robust evidence exists on caffeine and fluid management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, cafeinated beverages are considered to play an important role in inducing UI due to their diuretic efect. A prospective cohort study of more than 65,000 women found that excessive cafeine intake (≥450 mg/ day) was associated with an increased incidence of UI [5]. A case-control study demonstrated that high cafeine intake (≥400 mg/day) might cause detrusor overactivity which is related to UUI based on urodynamic evaluation [6].…”
Section: Dietary Modiicationsmentioning
confidence: 99%